Cropping systems in agriculture and their impact on soil health-A review - Yang, Tony; Siddique, Kadambot H.M.; Liu, Kui (Global ecology and conservation, 2020)
Soil health is defined as the capacity of soil to function, within ecosystem boundaries, to sustain crop and animal productivities, maintain or enhance environmental sustainability, and improve human health worldwide. In agro-ecosystems, the soil health can change due to anthropogenic activities, such as preferred cropping practices and intensive land-use management, which can further impact soil functions. Previous assessment of soil health in agriculture mostly relates to soil eco-functions that are integrated with non-biological properties such as soil nutrients and soil structures. In recent years, biological properties such as soil microorganisms were considered as an essential composition in soil health as well. However, systematic reviews of soil health and its potential feedback to human society under different cropping practices are still limited. In this review, we discussed 1) the impact of common and novel cropping practices in agro-systems on soil health, 2) the evolution of plant–microbe–soil complex and the biochemical mechanisms under the pressure of agriculture that responsible for soil health, 3) changes in the concept of soil quality and health over recent decades in agro-systems and the key indicators currently used for evaluating soil health, and 4) issues in agroecosystems that affect soil health the most, particularly how various cropping practices have developed over time with human activities in agroecosystem. This knowledge, along with necessary policies, will help to ensure healthy soil—a crucial component for sustainable ecosystem development. [Display omitted] •Introduced the development and recently refined content of soil health and quality.•Clarified influences of different cropping systems on soil health.•Discussed soil microbial impacts on soil health within soil-microbe-plant complex.•Highlighted indicators for soil health evaluation in various cropping systems.•Discussed soil degradation from cropping practices.